Criminal Policy in Law Enforcement of Criminal Acts of Drug Circulation in the Digital Era - Sidabutar, Ronny Nicolas; Danil, Elwi; Yunara, Edi; Mulyadi, Mahmud (KnE Social Sciences, 2024)
The process of proving narcotics trafficking cases in the digital era is closely related to the due process of law. However, if the proof process is carried out with legal defects, then the evidence obtained is also legally flawed, which renders it unusable as legal evidence before the trial. Considering this, the study aims to explore the criminal policy of law enforcement for narcotics trafficking in the digital era within the jurisdiction of Medan City, focusing on the factors that influence law enforcement and the criminal law enforcement policies for narcotics trafficking. This study adopts a normative legal research approach, using descriptive analysis and the statute approach. The data collection technique involves library research and interviews, with data analysis conducted through a qualitative method. The research results reveal that the most influential factor is the legal culture, as there is a stigma in law enforcement for narcotics crime, and everyone is suspected of being a dealer always seeking the lightest punishment and fast legal process. However, if the perpetrator is a narcotics user/abuser, there are Law Enforcement Officials who are unscrupulous and want the user to be subject to criminal sanctions as a dealer. In terms of law enforcement efforts, the penal policies carried out by law enforcement officials are still insufficient in eradicating narcotics trafficking in the digital era. The study suggests that with the support of the ITE Law regarding electronic evidence, law enforcement officials should be able to use these instruments in uncovering criminal cases to make it easier to prove. This is because, with the development of technology, information, and communication, the modes of drug trafficking are also growing rapidly. Keywords: criminal policy, digital era, narcotics circulation